2017
DOI: 10.1080/02770903.2017.1313270
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traffic-related air pollution on susceptibility to infantile bronchiolitis and childhood asthma: A cohort study in Korea

Abstract: TRAP appeared to be associated with an increased asthma among children with bronchiolitis, indicating the importance of modifying effects of bronchiolitis in asthma pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
4
30
0
Order By: Relevance
“…47 In contrast, studies that reported strong associations were conducted in places such as the United Kingdom, Poland, and South Korea, whose air pollution indexes were 40.63, 52.88, and 54.80, respectively. [23][24][25]48 Similar trends have been reported within the United States. A study conducted in Los Angeles reported that children and adults who suffer from asthma and live close to tra c are nearly three times more likely to visit the emergency department or be hospitalized than those who live near low tra c density.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…47 In contrast, studies that reported strong associations were conducted in places such as the United Kingdom, Poland, and South Korea, whose air pollution indexes were 40.63, 52.88, and 54.80, respectively. [23][24][25]48 Similar trends have been reported within the United States. A study conducted in Los Angeles reported that children and adults who suffer from asthma and live close to tra c are nearly three times more likely to visit the emergency department or be hospitalized than those who live near low tra c density.…”
Section: Discussionsupporting
confidence: 73%
“…Two previous studies in California and South Korea utilizing radial density measures similar to ours found effects only at much closer distances of 500 feet and 200 meters respectively, than the 1-mile buffer we used. 23,25 Only one other study, conducted in Minnesota, has utilized EHR data to assess the relationship between asthma exacerbation and tra c-related air pollution. 50 The authors used vehicle kilometers traveled within 250 meters and 500 meters of each individual's residence, as well as the tra c density as their exposures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary exposure in our study was the residential distances to two types of roadways: roads with U.S. Census feature Class Code A1 (55 + MPH with limited access only accessible via ramps) and A2 (35 + MPH-primary road without limited access), [32][33][34] with these speeds corresponding to highways and major roadways, respectively. 15,16,18,25 We abstracted the address information of each individual in our cohort from our EHR system and geocoded them using ArcGIS (version 10.5; ESRI Inc., Redlands, CA).…”
Section: Primary Exposurementioning
confidence: 99%